2021
DOI: 10.1002/mp.15276
|View full text |Cite
|
Sign up to set email alerts
|

The current status of preclinical proton FLASH radiation and future directions

Abstract: We review the current status of proton FLASH experimental systems, including preclinical physical and biological results. Technological limitations on preclinical investigation of FLASH biological mechanisms and determination of clinically relevant parameters are discussed. A review of the biological data reveals no reproduced proton FLASH effect in vitro and a significant in vivo FLASH sparing effect of normal tissue toxicity observed with multiple proton FLASH irradiation systems. Importantly, multiple studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 74 publications
(158 reference statements)
1
33
0
Order By: Relevance
“…Furthermore, as ensuring precise beam delivery and positioning is difficult, transmission or ‘ shoot-through ’ FLASH ( 186 ) with protons is performed where exploitation of the BP may be considered redundant to maintain a high, effective mean dose rate whilst also resulting in the FLASH effect ( 184 ). Several transmission studies have been reported ( 177 , 178 , 187 ) as this method is achievable with current technologies. This bypasses the need for additional beam modification devices, minimizing range uncertainties and delivery requirements.…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…Furthermore, as ensuring precise beam delivery and positioning is difficult, transmission or ‘ shoot-through ’ FLASH ( 186 ) with protons is performed where exploitation of the BP may be considered redundant to maintain a high, effective mean dose rate whilst also resulting in the FLASH effect ( 184 ). Several transmission studies have been reported ( 177 , 178 , 187 ) as this method is achievable with current technologies. This bypasses the need for additional beam modification devices, minimizing range uncertainties and delivery requirements.…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…The FLASH effect has been primarily studied in vivo models with electron beams of intermediate energy [2] and reproduced with other beams including proton beams at 60-160 Gy/s [3][4][5][6][7]. Electron beams are pulsed whereas proton beams are quasicontinuous; this inherent difference in temporal beam structure dictates major differences in instantaneous dose rates that might impact early physico-chemical and biological outcomes.…”
mentioning
confidence: 99%
“…Other papers in this issue highlight the variety of radiotherapy types used to deliver UHDR to date: electrons, photons, protons, and light ions. [47][48][49] Multimodality clinical trials will require careful consideration of machine capabilities, differences in dose prescriptions, radiobiology, etc. Early clinical trials would optimally be powered to see if different FLASH modalities caused different outcomes using patients as their own controls if possible.…”
Section: Critical Questions For Reproducibility In Clinical Trialsmentioning
confidence: 99%
“…Other papers in this issue highlight the variety of radiotherapy types used to deliver UHDR to date: electrons, photons, protons, and light ions 47‐49 . Multi‐modality clinical trials will require careful consideration of machine capabilities, differences in dose prescriptions, radiobiology, etc.…”
Section: Introductionmentioning
confidence: 99%